PELAKSANAAN URUSAN PEMERINTAHAN KONKUREN DINAS SOSIAL DI KOTA PEKANBARU (BIDANG REHABILITASI SOSIAL ANAK DALAM KEDISABILITASAN TAHUN 2017-2018) - Rizkiy A.Y, Fadhlunnisa; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Social Office in Pekanbaru is the government agency that held the government affairs in the social, one in the field of social rehabilitation. Children With Disability or generally known as ADK is one of the community with social prosperity issues that have an improper life in humanity way and become one of the targets in the implementation of social rehabilitation. The establishment of the Social Ministerial Regulation No. 7 of 2017 aims to implement the social rehabilitation of ADK in accordance with the standard of social habilitation and rehabilitation of persons with disabilities. The problems of this study are (1) how do the implementation of concurrent government affairs of Social Office in Pekanbaru (the field of social rehabilitation of children with disability in 2017-2018)? (2) what are the obstacle factors in the implementation of concurrent government affairs of Social Office in Pekanbaru (the field of social rehabilitation of children with disability in 2017-2018)?This study aimed to describe the implementation of concurrent government affairs of Social Office in Pekanbaru (the field of social rehabilitation of children with disability in 2017-2018) and the obstacle factors in the implementation of concurrent government affairs. The study location was conducted at Social Office in Pekanbaru. The data collection technique was done through interviews and documentation. The data analysis technique used in this study was interactive analysis model. The results of this study is that the implementation of concurrent government affairs at Social Office in Pekanbaru (the field of social rehabilitation of children with disability in 2017-2018) in the form of coordination of data collection, provision of social assistance, as well as further guidance for persons with disabilities including ADK. The obstacle factors in the implementation of concurrent government affairs at Social Office in Pekanbaru (the field of social rehabilitation of children with disability in 2017-2018) is no Draft of Regional Regulation or Regulations of Governing Mayor specifically in the implementation of the social rehabilitation of ADK in Pekanbaru, the limited budgetary and human resources (HR), and the absence of a specific case of ADK that can be conducted the social rehabilitation, for instance ADK in trouble with the law and ADK with the victims of violence.Keywords: Concurrent Government Affairs, Authority Social Affairs, Social Rehabilitation of Children with Disability